Functional Programming Oriented Software Design: A Systematic Literature Review - Camarillo-Villa, Jose Daniel; Limon, Xavier; Cortes-Verdin, Karen; Sanchez-Garcia, Angel J. (2023 11th International Conference in Software Engineering Research and Innovation (CONISOFT), 2023)
In recent years, there has been a renewed interest in Functional Programming (FP) as it has become a popular programming paradigm in several languages, including Python and JavaScript. Additionally, Functional Programming is the primary paradigm for increasingly used languages such as Clo-jure and Haskell, which have taken on significant importance for researchers and developers alike. FP has several benefits in software development, providing readable, maintainable, and scalable systems. However, despite these benefits, most of the literature related to software design currently lacks clear and detailed specifications concerning the functional paradigm. In contrast, Object-Oriented Programming, for instance, possesses a vast array of design resources and tools. This and other challenges can make the adoption of FP difficult for developers who seek to integrate the FP paradigm in their systems. The objective of the research work is to present the state of the art of FP-oriented software design, covering method-ologies, practices, and artefacts; analysing different proposals, and identifying open challenges. To arhieve the objective, a Systematic Literature Review (SRL) was conducted, following the Kitchenham's guidelines. We found a total of 14 primary studies published between 2012 and 2022, covering different artefacts and practices for software design under FP. Although Software design under FP is currently a little-explored topic in Software Engineering, its importance in software development is undeniable, and its use is expected to continue growing, being an interesting opportunity area for future research.